Evaluation and academic training of teachers in a public educational institution in the vicinity of Lima - Castillo Olivares , Vidal (2024)
The objective of this research was to determine the relationship between academic evaluation and the professional training of teachers in a public educational institution in the Cercado de Lima. The study followed a non-experimental, correlational design. The sample consisted of 60 teachers. A Likert scale and a questionnaire were used as instruments. It was concluded that there is a positive relationship between academic evaluation and the professional training of teachers in this public educational institution in the Cercado de Lima.